State-Business Alliances and Economic Development : Turkey, Mexico and North Africa. - Özel, Isik (Routledge Political Economy of the Middle East and North Africa., 2014)
This book argues that a key dynamic behind economic development in the emerging markets is the coordination between the state and businesses. Exploring the links between institutions, state--business alliances and economic development in the context of tumultuous market transitions since the 1980s, the book tackles the formation and sustainability of coordination-inducing institutions besides their mere existence, and points out the new modalities of coordination in the age of new developmentalism. Based on extensive original research in Turkey and Mexico embedded in a comparative historica.